PENGARUH CITRA MEREK DAN LOKASI DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA TOKO HW BAKERY SITUBONDO DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Riantika, Yuni; Arief, Muhammad Yahya; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2022)
HW bakery Situbondo shop is a business engaged in the food business. Until now, HW bakery Situbondo continues to grow. The purpose of this study was to analyze and test the effect of Brand Image and Location in determining Purchase Decisions at the HW Bakery Situbondo Store with Consumer Trust as an Intervening Variable. This research is an explanatory research. The population in this study was HW Bakery Situbondo. The sampling technique was determined by quata sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Brand Image has a significant effect on consumer trust, Location has a significant effect on consumer trust, Brand Image has a negative but not significant effect on purchasing decisions Location has a significant effect on purchasing decisions, consumer trust has a significant effect on Buyer's decision. The results of the indirect effect hypothesis test show that the Brand Image variable has a significant effect on Purchase Decisions through Consumer Trust, Location has a significant effect on Purchase Decisions through Consumer Trust,